Presentation of Selected Bioethical Deliberative Models in Clinical Decision-Making: Reflections on a Case of Severe Hypoxic–Ischemic Encephalopathy in a Newborn. Case Report (Revista Iberoamericana de Bioética, 2026)
The bioethical dilemmas arising in medical practice due to technological advances in recent decades have generated particular interest in Neonatal Intensive Care Units (NICUs) and among the multidisciplinary teams responsible for caring for this age group. The methodological analysis of the main bioethical conflicts faced by healthcare personnel in daily practice supports more accurate decision-making. This article describes the case of a newborn that presented an ethical dilemma within the therapeutic framework of the NICU treatment team at Hospital Universitario San Ignacio (Bogotá, Colombia), and examines it using several deliberative methodologies described in the literature (Diego Gracia’s model, the casuistic method, convergence ethics, and QUAR+), the implementation of which may be highly useful in everyday pediatric practice.
Keywords: theoretical models; encephalopathy; end-of-life decision-making